Crosslinker composition for olefin-based copolymer, sealant composition for optical device comprising same, and sealant film for optical device

The low productivity of ethylene/α-olefin copolymers is solved by using a crosslinker composition containing propyl 3-(triallylsilyl)acrylate and triallyl isocyanurate and low productivity of ethylene/α-olefin copolymers and The problem of poor miscibility achieves high volume resistance and excellent insulation, and is suitable for solar cell sealants.

CN119301187APending Publication Date: 2025-01-10LG CHEM LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202380043639.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-07-11
Filing Date
2023-07-10
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

The productivity of ethylene/α-olefin copolymers in existing solar cell sealants is low and the miscibility with polar crosslinking additives is poor, which affects the volume resistance and insulation of the material.

Method used

A crosslinking agent composition has been developed, including crosslinking additives such as 3-(triallylsilyl)acrylate and triallyl isocyanurate for enhancing the ethylene/α-olefin copolymers. Missoluble and cross-linking properties form sealants with high volume resistance and excellent insulation.

Benefits of technology

The impregnation rate and crosslinking degree of ethylene/α-olefin copolymer are significantly improved, and high volume resistance and light transmittance are achieved, which are suitable for use in the electrical and electronic industries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005158774060000031
    Figure BDA0005158774060000031
  • Figure BDA0005158774060000041
    Figure BDA0005158774060000041
  • Figure BDA0005158774060000051
    Figure BDA0005158774060000051
Patent Text Reader

Abstract

The present invention relates to a crosslinking agent composition for an olefin-based copolymer, a sealing agent composition for an optical device, a sealing film for an optical device, and a photoelectric device, in a cross-linking agent composition for an olefin-based copolymer or a sealant composition for an optical device containing an olefin-based copolymer, a compound of formula 1 is used as a cross-linking assistant, thus, a sealant composition for an optical device and a sealant film for an optical device, which exhibit excellent productivity and high volume resistance and light transmittance, are formed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application claims the benefit of Korean Patent Application No. 10-2022-0085134 filed on July 11, 2022 in the Korean Intellectual Property Office, the contents of which are incorporated into this specification by reference.

[0002] The present invention relates to a cross-linking agent composition for an olefin copolymer, a sealant composition for an optical device comprising the cross-linking agent composition, and a sealing film for an optical device, and relates to a cross-linking agent composition for an olefin copolymer used in a sealant composition for an optical device comprising the olefin copolymer, a sealant composition for an optical device comprising the cross-linking agent composition, a sealing film for an optical device manufactured using the sealant composition, and an optical device module comprising the sealing film for an optical device. Background Art

[0003] As global environmental problems, energy problems, etc. become more and more serious, solar cells are attracting attention as a means of generating clean energy without worrying about exhaustion. If solar cells are used outdoors, such as on the roof of a building, a module type is used. In order to obtain a crystalline solar cell module when manufacturing a solar cell module, a protective sheet (surface side transparent protective member) / solar cell sealant / crystalline solar cell device / solar cell sealant / protective sheet (back side protective member) for a solar cell module is laminated in sequence. At the same time, in order to manufacture a thin-film solar cell module, a thin-film type solar cell device / solar cell sealant / protective sheet (back side protective member) for a solar cell module is laminated in sequence.

[0004] As a solar cell sealant, ethylene / vinyl acetate copolymer or ethylene / α-olefin copolymer is generally used. In addition, in the solar cell sealant, considering the need for long-term weather resistance, a light stabilizer is generally included as an additive. In addition, considering the adhesion of a transparent surface side protective member or a back side protective member represented by glass, a silane coupling agent is generally included in the solar cell sealant.

[0005] Specifically, ethylene / vinyl acetate copolymer (EVA) sheets are widely used due to their excellent transparency, flexibility and adhesion. Ethylene / vinyl acetate copolymer (EVA) films are widely used due to their excellent transparency, flexibility and adhesion. However, if the EVA composition is used as a constituent material of a solar cell sealant, it is understood that components such as acetic acid gas generated by the decomposition of EVA may affect the solar cell device.

[0006] Ethylene / α-olefin copolymers do not have the hydrolysis problem of resins and can solve the problem of life or reliability degradation. However, since ethylene / α-olefin copolymers do not contain polar groups in resins, their miscibility with polar crosslinking aids contained as constituent materials of conventional solar cell sealants deteriorates, impregnation requires a long time, and there are productivity problems.

[0007] As described above, there is still a need to develop a crosslinking aid that can improve the productivity of a solar cell encapsulant containing an ethylene / α-olefin copolymer that can be effectively used as a material having excellent volume resistance and requiring high insulation, such as a solar cell encapsulant.

[0008] [Prior art literature]

[0009] [Patent Document]

[0010] (Patent Document 1) Korean Patent Publication No. 2018-0063669 Summary of the invention

[0011] Technical issues

[0012] One task to be solved in the present invention is to provide a crosslinking agent composition for olefin-based copolymers, which is used for crosslinking olefin-based copolymers and contains a crosslinking auxiliary agent having excellent miscibility with the olefin-based copolymers.

[0013] Another task to be solved in the present invention is to provide a sealant composition for optical devices, which contains a cross-linking auxiliary agent having excellent miscibility with the olefin-based copolymer and thus exhibits high volume resistance and excellent insulation properties.

[0014] Still another task to be solved in the present invention is to provide a sealing film for an optical device, the sealing film being manufactured by using the sealant composition for an optical device.

[0015] Still another task to be solved in the present invention is to provide a photoelectric device including the sealing film for an optical device.

[0016] Technical Solution

[0017] In order to solve the above-mentioned tasks, the present invention provides a crosslinking agent composition for an olefin copolymer, a sealant composition for an optical device, a sealing film for an optical device, and a photovoltaic device.

[0018] [1] The present invention provides a crosslinking agent composition for olefin copolymers, comprising: a compound of formula 1.

[0019] [Formula 1]

[0020]

[0021] In Formula 1, R1 to R4 are each independently an alkyl group of 1 to 20 carbon atoms or an alkenyl group of 2 to 20 carbon atoms, and m is an integer of 1 to 20.

[0022] [2] The present invention provides a crosslinking agent composition for olefin copolymers according to [1], wherein R1 to R4 are each independently an alkenyl group having 2 to 8 carbon atoms, and m is an integer of 1 to 12.

[0023] [3] The present invention provides the crosslinking agent composition for olefin copolymers according to [1] or [2], wherein R1 to R4 are each independently an alkenyl group having 2 to 8 carbon atoms and having a double bond at its terminal.

[0024] [4] The present invention provides a crosslinking agent composition for olefin copolymers according to any one of [1] to [3], wherein the crosslinking aid compound of Formula 1 is 3-(triallylsilyl)propyl acrylate.

[0025] [5] The present invention provides the crosslinking agent composition for olefin copolymers according to [4], further comprising a second crosslinking aid compound in addition to the crosslinking aid compound of Formula 1.

[0026] [6] The present invention provides a crosslinking agent composition for olefin copolymers according to [5], wherein the weight ratio of the crosslinking aid compound of formula 1 to the second crosslinking aid compound is 1:0.2 to 1:9.

[0027] [7] The present invention provides a crosslinking agent composition for olefin copolymers according to [5] or [6], wherein the second crosslinking aid compound comprises one or more selected from triallyl isocyanurate, triallyl cyanurate, diallyl phthalate, diallyl fumarate, diallyl maleate, ethylene glycol diacrylate, ethylene glycol dimethacrylate and trimethylolpropane trimethacrylate.

[0028] [8] The present invention provides a crosslinking agent composition for an olefin copolymer according to any one of [1] to [7], wherein the crosslinking agent is one or more selected from an organic peroxide, a hydroperoxide and an azo compound.

[0029] [9] The present invention provides a crosslinking agent composition for olefin copolymers according to any one of [1] to [8], wherein the crosslinking agent is selected from tert-butyl cumyl peroxide, di-tert-butyl peroxide, dicumyl peroxide, 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane, 2,5-dimethyl-2,5-di(tert-butylperoxy)-3-hexyne, cumyl hydroperoxide, dicumyl hydroperoxide, 2,5-dimethyl-2,5-di(hydroperoxy)hexane, tert-butyl hydroperoxide, bis-3,5,5-trimethylhexanoyl peroxide, octanoyl peroxide, benzoyl peroxide, o-methylbenzoyl peroxide, One or more of 2,4-dichlorobenzoyl oxide, tert-butyl peroxyisobutyrate, tert-butyl peroxyacetate, tert-butyl peroxycarbonate-2-ethylhexyl ester (TBEC), tert-butyl peroxy-2-ethylhexanoate, tert-butyl peroxypivalate, tert-butyl peroxyoctanoate, tert-butyl peroxyisopropyl carbonate, tert-butyl peroxybenzoate, di-tert-butyl peroxyphthalate, 2,5-dimethyl-2,5-di(benzoylperoxy)hexane, 2,5-dimethyl-2,5-di(benzoylperoxy)-3-hexyne, methyl ethyl ketone peroxide, cyclohexanone peroxide, azobisisobutyronitrile and azobis(2,4-dimethylvaleronitrile).

[0030]

[10] The present invention provides a crosslinking agent composition for olefin copolymers according to any one of [1] to [9], wherein the silane coupling agent is one or more selected from N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane, N-(β-aminoethyl)-γ-aminopropylmethyldimethoxysilane, γ-aminopropyltriethoxysilane, γ-glycidoxypropyltrimethoxysilane, γ-methacryloxypropyltrimethoxysilane, vinyltrimethoxysilane, vinyltriethoxysilane, 3-methacryloxypropylmethyldimethoxysilane, 3-methacryloxypropylmethyldiethoxysilane, 3-methacryloxypropyltriethoxysilane and p-phenylvinyltrimethoxysilane.

[0031]

[11] In addition, the present invention provides a sealant composition for an optical device, comprising: an olefin-based polymer; and the cross-linking agent composition for an olefin-based copolymer according to any one of [1] to

[10] .

[0032]

[12] The present invention provides the sealant composition for optical devices according to

[11] , wherein the olefin copolymer is an ethylene α-olefin copolymer.

[0033]

[13] In addition, the present invention provides a sealing film for an optical device, which comprises a structure derived from an olefin-based copolymer and a compound of Formula 1.

[0034] [Formula 1]

[0035]

[0036] In Formula 1, R1 to R4 are each independently an alkyl group of 1 to 20 carbon atoms or an alkenyl group of 2 to 20 carbon atoms, and m is an integer of 1 to 20.

[0037]

[14] In addition, the present invention provides a photoelectric device comprising an optical device and the sealing film for an optical device according to

[13] .

[0038] Beneficial Effects

[0039] The crosslinking agent composition for olefin copolymers of the present invention contains a compound having excellent miscibility with the olefin copolymer as a crosslinking auxiliary agent, and is quickly impregnated into the olefin copolymer. The sealant composition for optical devices obtained using the crosslinking agent composition exhibits excellent volume resistance and light transmittance, and can be widely used for various purposes in the electrical and electronic industries. DETAILED DESCRIPTION

[0040] Hereinafter, the present invention will be described in more detail to help understanding of the present invention.

[0041] It should be understood that the words or terms used in the present disclosure and claims should not be understood as the meanings defined in commonly used dictionaries. It will be further understood that based on the inventors can appropriately define the meanings of words or terms to best illustrate the principles of the present invention, the words or terms should be understood to have the meanings consistent with their meanings in the context of the relevant technology and the technical concept of the present invention.

[0042] Each substituent defined in the present disclosure will be explained in detail below.

[0043] Unless otherwise specified, the term "alkyl" used in the present disclosure refers to a straight-chain or branched hydrocarbon residue.

[0044] Unless otherwise specified, the term "alkenyl" used in the present disclosure refers to a straight chain or branched chain alkenyl group.

[0045] The branched chain may be an alkyl group of 1 to 20 carbon atoms or an alkenyl group of 2 to 20 atoms.

[0046] [Crosslinking agent composition for olefin copolymer]

[0047] The crosslinking agent composition for an olefin-based copolymer includes: a crosslinking agent; a silane coupling agent; and a crosslinking auxiliary compound represented by Formula 1.

[0048] [Formula 1]

[0049]

[0050] In Formula 1, R1 to R4 are each independently an alkyl group of 1 to 20 carbon atoms or an alkenyl group of 2 to 20 carbon atoms, and m is an integer of 1 to 20.

[0051] In Formula 1, R1 to R4 may each independently be an alkenyl group of 2 to 8 carbon atoms, and m is an integer of 1 to 12.

[0052] In addition, in Formula 1, R1 to R4 may each independently be an alkenyl group of 2 to 8 carbon atoms having a double bond at a terminal thereof.

[0053] In addition, the crosslinking agent composition for an olefin-based copolymer according to one embodiment of the present invention may specifically include 3-(triallylsilyl)propyl acrylate represented by the following Formula 2 as the Formula 1 compound.

[0054] [Formula 2]

[0055]

[0056] The compound of formula 1 contained in the crosslinking agent composition for olefin copolymers of the present invention can be contained in the crosslinking agent composition for olefin copolymers as a crosslinking aid, and the compound of formula 1 can show excellent miscibility with the olefin copolymers, and can show a fast impregnation rate. Thus, the absorption rate of the crosslinking aid that shows the slowest absorption rate in the olefin copolymer among the crosslinking agent, silane coupling agent and crosslinking aid contained in the conventional crosslinking agent composition for olefin copolymers can be increased, and the impregnation time of the crosslinking agent composition can be reduced, a short impregnation time can be achieved, and excellent crosslinking performance for the olefin copolymer can be shown.

[0057] If the crosslinking agent composition for olefin-based copolymers of the present invention including the compound of Formula 1 is applied as a crosslinking agent to a sealant composition for optical devices including an olefin-based copolymer, the sealant composition for optical devices may show a high degree of crosslinking as well as high volume resistance and transmittance.

[0058] In addition, the crosslinking agent composition for an olefin-based copolymer may further include a second crosslinking aid compound as a crosslinking aid in addition to the crosslinking aid compound of Formula 1.

[0059] As the second cross-linking auxiliary agent, various cross-linking auxiliary agents known in the art may be used, for example, a compound including at least one unsaturated group such as an allyl group and a (meth)acryloyloxy group may be used.

[0060] The second cross-linking aid may be a cross-linking aid containing at least one unsaturated group, and may be, for example, a polyallyl compound such as triallyl isocyanurate (TAIC), triallyl cyanurate, diallyl phthalate, diallyl fumarate, and diallyl maleate, and the compound containing a (meth)acryloyloxy group may be, for example, a poly(meth)acryloyloxy compound such as ethylene glycol diacrylate, ethylene glycol dimethacrylate, and trimethylolpropane trimethacrylate, but is not particularly limited.

[0061] If the crosslinking agent composition for olefin-based copolymers according to one embodiment of the present invention further includes a second crosslinking aid compound in addition to the compound of Formula 1, the weight ratio of the compound of Formula 1 to the second crosslinking aid compound may be 1:0.20 to 9.0, specifically, 1:0.20 to 6.0, 1:0.20 to 5.0, 1:0.20 to 4.0, 1:0.20 to 3.7, 1:0.25 to 5.0, 1:0.25 to 4.0, 1:0.25 to 3.7, 1:0.25 to 3.5, 1:0.25 to 3.2, 1:0.25 to 3.0, 1:0.3 to 3.7, 1:0.3 to 3.5, 1:0.3 to 3.2, 1:0.3 to 3.0, or 1:0.33 to 3.0.

[0062] If the cross-linking agent composition for olefin-based copolymers according to one embodiment of the present invention includes the compound of Formula 1 and a second cross-linking auxiliary compound together, an even higher degree of cross-linking can be achieved compared to the case where only the same amount of the compound of Formula 1 is included, and if applied to a sealant composition for optical devices, the sealant composition for optical devices can show high volume resistance and can satisfy excellent light transmittance and adhesion.

[0063] If the compound of Formula 1 is included together with the second crosslinking aid, and if the ratio of the second crosslinking aid to the compound of Formula 1 is increased to a certain extent or more, the degree of crosslinking can be increased, and the vulcanization performance can be improved, and if the ratio of the second crosslinking aid to the compound of Formula 1 is reduced, the degree of reduction in the impregnation rate can be reduced. Therefore, an appropriate ratio can be determined within the above range according to the physical properties to be displayed. If the ratio of the second crosslinking aid is too large, it may be difficult to show the improvement effect on the impregnation rate by using the compound of Formula 1, and if the ratio of the second crosslinking aid is too small, it is difficult to properly show the additional effect that can be achieved by mixing the second crosslinking aid.

[0064] In the cross-linking agent composition for olefin-based copolymers according to one embodiment of the present invention, in order to achieve reduced impregnation time of the cross-linking agent and excellent vulcanization performance, cross-linking degree and volume resistance, the compound of Formula 1 and the second cross-linking aid compound may be included together, and the compound of Formula 1 and the second cross-linking aid compound may be included in a weight ratio of 1:0.20 to 3.7, specifically, 1:0.25 to 3.7, 1:0.25 to 3.5, 1:0.25 to 3.2, 1:0.25 to 3.0, 1:0.3 to 3.7, 1:0.3 to 3.5, 1:0.3 to 3.2, 1:0.3 to 3.0, or 1:0.33 to 3.0.

[0065] The crosslinking agent may use various crosslinking agents known in the art as long as they are crosslinkable compounds that can initiate free radical polymerization or form crosslinked bonds, and one or more selected from organic peroxides, hydroperoxides and azo compounds may be used.

[0066] Furthermore, in one embodiment of the present invention, the crosslinking agent may specifically be an organic peroxide.

[0067] The organic peroxide may be an organic peroxide having a one-hour half-life temperature of 120°C to 135°C, for example, 120°C to 130°C, 120°C to 125°C, specifically, 121°C. The "one-hour half-life temperature" refers to the temperature at which the half-life of the crosslinking agent becomes one hour. Depending on the one-hour half-life temperature, the temperature at which the free radical initiation reaction is effectively performed may become different. Therefore, in the case of using an organic peroxide having a one-hour half-life temperature within the above range, the free radical initiation reaction, i.e., the crosslinking reaction at the lamination process temperature for manufacturing a photovoltaic device, may be effectively performed.

[0068] The crosslinking agent may include one or more selected from the following: dialkyl peroxides, such as tert-butyl isopropyl peroxide, di-tert-butyl peroxide, diisopropyl peroxide, 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane and 2,5-dimethyl-2,5-di(tert-butylperoxy)-3-hexyne; hydroperoxides, such as isopropyl hydroperoxide, diisopropyl hydroperoxide, 2,5-dimethyl-2,5-di(hydroperoxy)hexane and tert-butyl hydroperoxide; diacyl peroxides, such as di-3,5,5-trimethylhexanoyl peroxide, octanoyl peroxide, benzoyl peroxide, o-methylbenzoyl peroxide and 2,4-dichlorobenzoyl peroxide; peroxyesters, such as Such as tert-butyl peroxyisobutyrate, tert-butyl peroxyacetate, tert-butyl peroxycarbonate-2-ethylhexyl ester (TBEC), tert-butyl peroxy-2-ethylhexanoate, tert-butyl peroxypivalate, tert-butyl peroxyoctanoate, tert-butyl peroxyisopropyl carbonate, tert-butyl peroxybenzoate, di-tert-butyl peroxyphthalate, 2,5-dimethyl-2,5-di(benzoylperoxy)hexane and 2,5-dimethyl-2,5-di(benzoylperoxy)-3-hexyne; ketone peroxides such as methyl ethyl ketone peroxide and cyclohexanone peroxide, lauryl peroxide; and azo compounds such as azobisisobutyronitrile and azobis(2,4-dimethylvaleronitrile), but without limitation.

[0069] The silane coupling agent that can be used is, for example, one or more selected from N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane, N-(β-aminoethyl)-γ-aminopropylmethyldimethoxysilane, γ-aminopropyltriethoxysilane, γ-glycidoxypropyltrimethoxysilane, γ-methacryloxypropyltrimethoxysilane (MEMO), vinyltrimethoxysilane, vinyltriethoxysilane, 3-methacryloxypropylmethyldimethoxysilane, 3-methacryloxypropylmethyldiethoxysilane, 3-methacryloxypropyltriethoxysilane and p-phenylvinyltrimethoxysilane.

[0070] The crosslinking agent composition for olefin-based copolymers may include 20 to 80 parts by weight of a crosslinking agent, 5 to 30 parts by weight of a silane coupling agent, and 10 to 60 parts by weight of a crosslinking aid including the crosslinking aid of Formula 1. The amount of the components may refer to a relative ratio between the weights of the components included in the crosslinking agent composition for olefin-based copolymers.

[0071] In the crosslinker composition for olefin copolymers, the content of the crosslinker may be 20 to 80 parts by weight, specifically, 20 or more parts by weight, 25 or more parts by weight, 30 or more parts by weight, 35 or more parts by weight, or 40 or more parts by weight to 80 or less parts by weight, 75 or less parts by weight, or 70 or less parts by weight. If the content of the crosslinker is too little, it is difficult to carry out a crosslinking reaction when using the olefin copolymer; if the content of the crosslinker is too large, the volume resistance of the sealant for optical devices manufactured by using the olefin copolymer may be reduced. Therefore, if the content of the crosslinker in the crosslinker composition for olefin copolymers is within the above range, the sealant composition for optical devices using the crosslinker composition can undergo an appropriate crosslinking reaction to form a sealant for optical devices, and the sealant for optical devices manufactured thereby can show a high volume resistance.

[0072] In the crosslinking agent composition for olefin copolymers, the content of the silane coupling agent can be 5 parts by weight to 30 parts by weight, specifically, 5 parts by weight or more, 6 parts by weight or more, 7 parts by weight or more, or 8 parts by weight or more to 20 parts by weight or less, 19 parts by weight or less, or 18 parts by weight or less. If the content of the silane coupling agent is too little, when the olefin copolymer is used, the sealant composition for optical devices has low adhesion to the substrate, for example, the sealant composition for optical devices has low adhesion to the glass substrate, and it is difficult to show the appropriate performance as a sealant for optical devices. If the content of the silane coupling agent is too large, the volume resistance of the sealant for optical devices may be inappropriately reduced. If the content of the silane coupling agent in the crosslinking agent composition for olefin copolymers is within the above range, the sealant composition for optical devices using the crosslinking agent composition can show excellent adhesion to the substrate of the optical device or the glass substrate where the optical device is located, can effectively prevent the penetration of moisture, the optical device can maintain excellent performance for a long time, and the sealant for optical devices can show high volume resistance.

[0073] The total amount of the crosslinking aid included in the crosslinking agent composition for olefin copolymers can be 10 parts by weight to 60 parts by weight, specifically, 11 parts by weight or more, 12 parts by weight or more, or 13 parts by weight or more and 60 parts by weight or less, 55 parts by weight or less, or 50 parts by weight or less, the crosslinking aid includes the crosslinking aid compound of Formula 1, that is, the crosslinking aid compound of Formula 1 as the crosslinking aid, or the crosslinking aid compound of Formula 1 and a second crosslinking aid compound.

[0074] The olefin-based copolymer to which the cross-linking agent composition for an olefin-based copolymer can be applied may satisfy, for example, (a) a density of 0.85 to 0.90 g / cc, and (b) a melt index of 0.1 to 100 g / 10 min.

[0075] The density (a) of the olefin copolymer may specifically be 0.850 g / cc or more, 0.855 g / cc or more, 0.860 g / cc or more, 0.865 g / cc or more, or 0.870 g / cc or more to 0.900 g / cc or less, 0.895 g / cc or less, 0.890 g / cc or less, 0.885 g / cc or less, or 0.880 g / cc or less. If the density of the olefin copolymer is too high, the transmittance of the sealant composition for optical devices using the olefin copolymer and the sealant for optical devices manufactured using the sealant composition may be reduced due to the crystalline phase contained in the olefin copolymer, but if the olefin copolymer satisfies the above density range, high transmittance can be exhibited.

[0076] The melt index (b) of the olefin copolymer may be 0.1 g / 10 min or more, 0.5 g / 10 min or more, 1.0 g / 10 min or more, 1.5 g / 10 min or more, 2.0 g / 10 min or more, 2.5 g / 10 min or more, 3.0 g / 10 min or more, or 3.5 g / 10 min or more and 100 g / 10 min or less, 95 g / 10 min or less, 90 g / 10 min or less, 85 g / 10 min or less, 80 g / 10 min or less, 75 g / 10 min or less, or 70 g / 10 min or less, 60 g / 10 min or less, or 50 g / 10 min or less. If the melt index of the olefin copolymer deviates from the above range and is too low or too high, there may be a problem that the moldability of the sealant composition for optical devices is deteriorated and stable extrusion becomes difficult. However, if the olefin-based copolymer satisfies the above-mentioned melt index range, the moldability of the sealant composition for optical devices may be excellent, and the sealant for optical devices and the sealing sheet for optical devices may be stably extruded.

[0077] The olefin-based copolymer to which the cross-linking agent composition for an olefin-based copolymer according to one embodiment of the present invention is applied may specifically be an ethylene / α-olefin copolymer.

[0078] Generally, the density of ethylene / α-olefin copolymers may be affected by the type and amount of monomers used in the polymerization process, the degree of polymerization, etc., and in the case of copolymers, is greatly affected by the amount of comonomers. As the amount of comonomers increases, ethylene / α-olefin copolymers with low density can be prepared, and the amount of comonomers that can be introduced into the copolymer may depend on the inherent copolymerization properties of the catalyst.

[0079] The ethylene / α-olefin copolymer to which the crosslinking agent composition for olefin copolymers of the present invention is applied can show low density and excellent processability as described above.

[0080] The ethylene / α-olefin copolymer is prepared by copolymerizing ethylene with an α-olefin monomer, in which case the α-olefin refers to a portion of the α-olefin monomer in the copolymer, which may be an α-olefin of 3 to 20 carbon atoms, specifically propylene, 1-butene, 1-pentene, 4-methyl-1-pentene, 1-hexene, 1-heptene, 1-octene, 1-decene, 1-undecene, 1-dodecene, 1-tetradecene, 1-hexadecene, 1-eicosene, etc., and any one of them or a mixture of two or more thereof may be used. The α-olefin may be 1-butene, 1-hexene or 1-octene, specifically 1-butene, 1-hexene or a combination thereof.

[0081] Furthermore, in the ethylene / α-olefin copolymer, the α-olefin content may be appropriately selected within the range satisfying physical conditions, specifically, greater than 0 mol% to 99 mol% or 10 mol% to 50 mol%, without limitation.

[0082] In addition, the olefin copolymer may have a volume resistivity of 1.0×10 15 Ω·cm or more, specifically, 3.0×10 15 Ω·cm or more, 5.0×10 15 Ω·cm or 7.0×10 15 Ω·cm or more of an ethylene α-olefin copolymer. If the volume resistivity of the olefin copolymer is too low, the volume resistivity of the sealant composition for optical devices after crosslinking may not reach a suitable level, but if the volume resistivity of the olefin copolymer satisfies the above value, the sealant composition for optical devices after crosslinking can show excellent volume resistivity. There is no particular upper limit on the volume resistivity of the olefin copolymer, but, considering the volume resistivity generally shown by the olefin copolymer and the difficulty in preparing the olefin copolymer with high volume resistivity, it can be 9.9×10 17 Ω·cm or less, 9.0×10 17 Ω·cm or less, 7.0×10 17 Ω·cm or less.

[0083] [Sealant composition for optical devices]

[0084] The crosslinking agent composition for olefin copolymers of the present invention can be used together with olefin copolymers to form a sealant composition for optical devices. The present invention provides a sealant composition for optical devices, which comprises an olefin polymer and a crosslinking agent composition for olefin copolymers.

[0085] The explanations about the olefin-based copolymer and the sealant composition for optical devices are the same as those mentioned above.

[0086] Based on 100 parts by weight of the sealant composition for optical devices, the content of the olefin copolymer can be 80 parts by weight to 99.5 parts by weight, specifically, 80 parts by weight or more, 82 parts by weight or more, 85 parts by weight or more, 86 parts by weight or more, 87 parts by weight or more, or 88 parts by weight or more to 99.5 parts by weight or less, 99 parts by weight or less, or 98.5 parts by weight or less. If the content of the olefin copolymer in the sealant composition for optical devices is too small, it may be difficult to show the appropriate mechanical properties of the sealant for optical devices such as tear resistance and tear strength. If the content of the olefin copolymer in the sealant composition for optical devices is within the above range, it can show appropriate mechanical properties as a sealant for optical devices.

[0087] Based on 100 parts by weight of olefin copolymer, the crosslinking agent composition for olefin copolymer according to one embodiment of the present invention can be used in an amount of 0.5 to 20 parts by weight. Based on 100 parts by weight of olefin copolymer, the crosslinking agent composition for olefin copolymer can be specifically used in an amount of more than 0.5 parts by weight, more than 0.7 parts by weight, more than 0.8 parts by weight, more than 1 parts by weight, more than 1.1 parts by weight, more than 1.2 parts by weight, more than 1.3 parts by weight, more than 1.4 parts by weight or more than 1.5 parts by weight to less than 20 parts by weight, less than 18 parts by weight, less than 15 parts by weight, less than 10 parts by weight, less than 8 parts by weight, less than 6 parts by weight, less than 5 parts by weight or less than 3 parts by weight. If the usage amount of the crosslinking agent composition is too little relative to the olefin copolymer, the crosslinking reaction is difficult to occur, and if the usage amount of the crosslinking agent composition is too large, the volume resistance of the sealant for optical devices may be reduced. If the crosslinker composition is used in the above ratio relative to the olefin-based copolymer, the sealant composition for optical devices using the crosslinker composition can undergo an appropriate crosslinking reaction to form a sealant for optical devices, and the sealant for optical devices thus manufactured can show high volume resistance.

[0088] In the sealant composition for optical devices according to one embodiment of the present invention, the content of the crosslinking aid compound of formula 1 can be 0.1 to 9 parts by weight based on 100 parts by weight of the olefin copolymer. Based on 100 parts by weight of the olefin copolymer, the content of the crosslinking aid compound of formula 1 can be specifically 0.1 parts by weight or more, 0.2 parts by weight or more, 0.3 parts by weight or more, or 0.4 parts by weight or more to 9 parts by weight or less, 8 parts by weight or less, 7 parts by weight or less, 6 parts by weight or less, 5 parts by weight or less, 4 parts by weight or less, 3 parts by weight or less or 2 parts by weight or less. If the crosslinking aid compound of formula 1 and the second crosslinking aid compound are used together as a crosslinking aid, the total amount can meet the above range. If the amount of the crosslinking aid is too small relative to the olefin copolymer, it is difficult to induce a crosslinking reaction. If the amount of the crosslinking aid is too large, the volume resistivity of the sealant for optical devices may be reduced. If the cross-linking auxiliary agent is included in the above ratio relative to the olefin-based copolymer, the sealant composition for optical devices may induce an appropriate cross-linking reaction to form a sealant for optical devices, and the sealant for optical devices thus formed may show high volume resistance.

[0089] Furthermore, the sealant composition for optical devices may further appropriately contain various additives known in the art in addition to the above-mentioned components, depending on applicable uses.

[0090] As the additive, one or more additives selected from the group consisting of a light stabilizer, a UV absorber, and a heat stabilizer may be used.

[0091] According to the purpose of the applied composition, the light stabilizer can capture the photothermally induced active species of the resin to prevent photooxidation. There is no particular limitation on the type of light stabilizer used, for example, known compounds such as hindered amine compounds and hindered piperidine compounds can be used.

[0092] According to the purpose, the UV absorber can absorb ultraviolet rays from sunlight and the like, convert them into harmless heat energy in the molecule, and play a role in preventing the photothermal-induced excitation of active substances in the resin composition. There is no particular limitation on the specific type of the UV absorber used, for example, one or a mixture of two or more of benzophenones, benzotriazoles, acrylonitriles, metal complexes, hindered amines, inorganic UV absorbers including ultrafine particles of titanium oxide and ultrafine particles of zinc oxide, etc. can be used.

[0093] In addition, the thermal stabilizer may include phosphorus-based thermal stabilizers such as tris(2,4-di-tert-butylphenyl)phosphite, phosphorous acid, bis[2,4-bis(1,1-dimethylethyl)-6-methylphenyl]ethyl ester, tetrakis(2,4-di-tert-butylphenyl)[1,1-biphenyl]-4,4'-diylbisphosphonate and bis(2,4-di-tert-butylphenyl)pentaerythritol diphosphite; and lactone-based thermal stabilizers such as the reaction product of 8-hydroxy-5,7-di-tert-butyl-furan-2-one and o-xylene, and one or two or more thereof may be used.

[0094] There is no particular limitation on the amount of light stabilizer, UV absorber and / or heat stabilizer. That is, the amount of additives can be appropriately selected in consideration of the use of the resin composition, the shape or density of the additives, etc. Generally, the amount can be appropriately controlled within the range of 0.01 to 5 parts by weight based on 100 parts by weight of the total solid content of the sealant composition for optical devices.

[0095] In addition, the sealant composition for optical devices can be used in various molded products by injection molding, extrusion molding, etc. Specifically, the composition can be used in various optoelectronic devices, for example, as a sealant for encapsulating devices in solar cells, and can be used as an industrial material applied in a lamination process such as heating, but is not limited thereto.

[0096] Furthermore, the present invention provides a sealing film for an optical device, the sealing film being manufactured by using the sealant composition for an optical device.

[0097] The sealing film for an optical device according to one embodiment of the present invention may include a structure derived from an olefin-based copolymer and a cross-linking auxiliary compound of Formula 1.

[0098] [Formula 1]

[0099]

[0100] In Formula 1, R1 to R4 are each independently an alkyl group of 1 to 20 carbon atoms or an alkenyl group of 2 to 20 carbon atoms, and m is an integer of 1 to 20.

[0101] The explanations about the olefin-based copolymer and the cross-linking auxiliary compound of Formula 1 are the same as above.

[0102] In addition, a sealing film for an optical device according to another embodiment of the present invention may include a structure derived from the cross-linking auxiliary compound of Formula 1 and a second cross-linking auxiliary compound.

[0103] The explanation about the second cross-linking auxiliary compound and the explanation about the case where the cross-linking auxiliary compound of Formula 1 and the second cross-linking auxiliary compound are used together as a cross-linking auxiliary are the same as above.

[0104] Furthermore, the present invention provides a photovoltaic device including the sealing film for an optical device.

[0105] Example

[0106] Hereinafter, the present invention will be explained in more detail with reference to Examples. However, the Examples are for illustration only, and the scope of the present invention is not limited thereto.

[0107] Example 1

[0108] 3-(Triallylsilyl)propyl acrylate [TPA, a product of TCI Co. (Tokyo Chemical Industry Co., Ltd.)] and triallyl isocyanurate (TAIC, a product of Sigma-Aldrich Co.) were mixed at 25 parts by weight and 75 parts by weight, respectively, to prepare a crosslinking aid.

[0109] 500 g of LUCENE® from LG Chem, an ethylene / 1-butene copolymer, was heated in a conventional oven at 40°C. TM LF675 dried overnight. LUCENE based on ASTM D1505 measurements TM The density of LF675 is 0.877g / cm 2 , and the melt index (190°C, 2.16kg) measured based on ASTM D1238 is 14.0g / 10min. The bowl temperature of the Haake modular torque viscometer is set to 40°C. The ethylene / α-olefin copolymer is injected into the bowl, and the crosslinker composition [1.00 parts (phr) of 1-(2-ethylhexyl) monoperoxycarbonate (TBEC, a product of Sigma Aldrich Co.) as a crosslinker, 0.50phr of a mixture of prepared TPA and TAIC (weight ratio 50:50) as a crosslinking aid, and 0.20phr of methacryloxypropyltrimethoxysilane (MEMO, a product of Shinetsu Co.) as a silane coupling agent] is injected using an electronic pipette. While stirring at 40 rpm at 40°C, the change in torque value over time is observed, the dipping is terminated when the torque value increases rapidly, and the dipping completion time of the crosslinker composition is measured.

[0110] Thereafter, by using the impregnated sample, a sheet-like sealing film having an average thickness of 0.5 mm was formed by press molding at a low temperature (under the condition of an extruder barrel temperature of 90 to 100° C.) without achieving high-temperature crosslinking.

[0111] Example 2

[0112] A crosslinking auxiliary was prepared by the same method as in Example 1 except that 3-(triallylsilyl)propyl acrylate (TPA) and triallyl isocyanurate (TAIC) were used as the crosslinking auxiliary in a mixing ratio of 50 parts by weight and 50 parts by weight, respectively, and then a sealing film was manufactured.

[0113] Example 3

[0114] A crosslinking aid was prepared by the same method as in Example 1 except that 3-(triallylsilyl)propyl acrylate (TPA) and triallyl isocyanurate (TAIC) were used as the crosslinking aid in a mixing ratio of 75 parts by weight and 25 parts by weight, respectively, and then a sealing film was manufactured.

[0115] Example 4

[0116] A crosslinking auxiliary agent was prepared by the same method as in Example 1, except that only 3-(triallylsilyl)propyl acrylate (TPA) was used as the crosslinking auxiliary agent and the injection amount was 0.25 phr instead of 0.50 phr, and then a sealing film was manufactured.

[0117] Example 5

[0118] A crosslinking auxiliary agent was prepared by the same method as in Example 1 except that only 3-(triallylsilyl)propyl acrylate (TPA) was used as the crosslinking auxiliary agent, and then a sealing film was manufactured.

[0119] Example 6

[0120] A crosslinking auxiliary was prepared by the same method as in Example 1 except that 3-(triallylsilyl)propyl acrylate (TPA) and triallyl isocyanurate (TAIC) were used as the crosslinking auxiliary in a mixing ratio of 10 parts by weight and 90 parts by weight, respectively, and then a sealing film was manufactured.

[0121] Example 7

[0122] A crosslinking auxiliary was prepared by the same method as in Example 1 except that 3-(triallylsilyl)propyl acrylate (TPA) and triallyl isocyanurate (TAIC) were used as the crosslinking auxiliary in a mixing ratio of 20 parts by weight and 80 parts by weight, respectively, and then a sealing film was manufactured.

[0123] Example 8

[0124] A crosslinking auxiliary was prepared by the same method as in Example 1 except that 3-(triallylsilyl)propyl acrylate (TPA) and triallyl isocyanurate (TAIC) were used as the crosslinking auxiliary in a mixing ratio of 80 parts by weight and 20 parts by weight, respectively, and then a sealing film was manufactured.

[0125] Comparative Example 1

[0126] A cross-linking auxiliary agent was prepared by the same method as in Example 1, except that only triallyl isocyanurate (TAIC) was used as the cross-linking auxiliary agent, and then a sealing film was manufactured.

[0127] In Table 1 below, crosslinking agent compositions used in Examples 1 to 8 and Comparative Example 1 are shown.

[0128] [Table 1]

[0129]

[0130]

[0131] Experimental example

[0132] Between two release films (thickness: about 100 μm), a sealing film with a thickness of 0.5 mm (10 cm×10 cm) was placed, and laminated and crosslinked in a vacuum laminator at a process temperature of 150° C. for a process time of 20 minutes (vacuum 5 minutes / pressure 1 minute / pressure holding 14 minutes).

[0133] (1) Impregnation rate

[0134] For each of Examples 1 to 8 and Comparative Example 1, the measured impregnation completion time of the crosslinking agent is recorded in Table 2 below.

[0135] (2) Volume resistance

[0136] The measurement was performed under the conditions of a temperature of 23±1° C. and a humidity of 50±3% by using an Agilent 4339B high resistance meter (Agilent Technologies, product of Kabushiki Kaish) while applying a voltage of 1,000 V for 600 seconds.

[0137] (3) Vulcanization performance

[0138] Based on ASTM D5280, the vulcanization performance was measured using the premier MDR from Alpha Technologies Co. The test was performed at 150°C for 20 minutes, and a torque curve varying with time was obtained. In this case, the condition of 150°C corresponds to the lamination temperature, and 20 minutes corresponds to the lamination time. In addition, the vulcanization performance between the samples was relatively compared using the difference between the maximum torque (MH) and the minimum torque (ML) applied by the MDR in the corresponding time period.

[0139] (4) Degree of crosslinking

[0140] Use scissors to cut the cross-linked sheets into 3x3 mm pieces.2 Dimensions. Closed with staples 7x14 cm 2 The sides and bottom of a 200-mesh wire mesh. The sheet was injected into the wire mesh, and the weight of the injected sheet was measured. The amount of the sheet was controlled to be 0.49 g to 0.51 g. After the sheet was injected, the top of the wire mesh was closed with staples, and the total weight of the sample was measured. A solution of 10 g of butylated hydroxytoluene (BHT) dissolved in 1,000 g of xylene was poured into a 2L cylindrical reactor, and three to four samples were injected into it. The reactor was heated, and after 5 hours from the starting boiling point, the reflux was terminated. The sample in the reactor was taken out using a metal scoop net and washed with xylene. The sample was vacuum dried overnight at 100°C. The weight of the dried sample was measured, and the degree of crosslinking was calculated. The degree of crosslinking was determined by the average of three to four samples refluxed in xylene.

[0141] Crosslinking degree (%) = [(sheet weight after reflow) / (sheet weight before reflow)] x 100

[0142] [Table 2]

[0143]

[0144] As shown in Table 2, if the crosslinking agent composition containing the crosslinking auxiliary compound of Formula 1 in Examples 1 to 8 is used, the impregnation completion time of the crosslinking agent can be shortened compared to Comparative Example 1 using triallyl isocyanurate as a crosslinking auxiliary. In addition, if a certain amount or more of the crosslinking auxiliary compound is used together with triallyl isocyanurate as a crosslinking auxiliary as in Examples 1 to 3 and Examples 6 to 8, the impregnation completion time of the crosslinking agent can be shortened, and a high degree of crosslinking and a high volume resistivity can be achieved.

Claims

1. A crosslinking agent composition for an olefin copolymer, the composition comprising: Cross-linking agent; Silane coupling agents; and The cross-linking auxiliary compound of the following formula 1: [Formula 1] In formula 1, R1 to R4 are each independently an alkyl group of 1 to 20 carbon atoms or an alkenyl group of 2 to 20 carbon atoms, m is an integer of 1 to 20.

2. The crosslinking agent composition for olefin copolymers according to claim 1, wherein R1 to R4 are each independently an alkenyl group of 2 to 8 carbon atoms, and m is an integer of 1 to 12.

3. The crosslinking agent composition for olefin copolymers according to claim 1, wherein R1 to R4 are each independently an alkenyl group of 2 to 8 carbon atoms having a double bond at its terminal.

4. The crosslinking agent composition for olefin copolymers according to claim 1, wherein The crosslinking auxiliary compound of Formula 1 is 3-(triallylsilyl)propyl acrylate. 5 . The crosslinking agent composition for olefin-based copolymers according to claim 1 , further comprising a second crosslinking aid compound in addition to the crosslinking aid compound of Formula 1.

6. The crosslinking agent composition for olefin copolymers according to claim 5, wherein The weight ratio of the cross-linking auxiliary compound of Formula 1 to the second cross-linking auxiliary compound is 1:0.2 to 1:

9.

7. The crosslinking agent composition for olefin copolymers according to claim 5, wherein The second crosslinking auxiliary compound includes one or more selected from triallyl isocyanurate, triallyl cyanurate, diallyl phthalate, diallyl fumarate, diallyl maleate, ethylene glycol diacrylate, ethylene glycol dimethacrylate and trimethylolpropane trimethacrylate.

8. The crosslinking agent composition for olefin copolymers according to claim 1, wherein The cross-linking agent is one or more selected from organic peroxides, hydroperoxides and azo compounds.

9. The crosslinking agent composition for olefin copolymers according to claim 1, wherein The crosslinking agent is selected from tert-butyl isopropyl peroxide, di-tert-butyl peroxide, diisopropyl peroxide, 2,5-dimethyl-2,5-di(tert-butyl peroxy)hexane, 2,5-dimethyl-2,5-di(tert-butyl peroxy)-3-hexyne, isopropyl hydroperoxide, diisopropyl hydroperoxide, 2,5-dimethyl-2,5-di(hydroperoxy)hexane, tert-butyl hydroperoxide, di-3,5,5-trimethylhexanoyl peroxide, octanoyl peroxide, benzoyl peroxide, o-methylbenzoyl peroxide, 2,4-dichlorobenzoyl peroxide, tert-butyl peroxide isobutyrate, One or more of tert-butyl peroxyacetate, tert-butyl peroxycarbonate-2-ethylhexyl ester (TBEC), tert-butyl peroxy-2-ethylhexanoate, tert-butyl peroxypivalate, tert-butyl peroxyoctanoate, tert-butyl peroxyisopropyl carbonate, tert-butyl peroxybenzoate, di-tert-butyl peroxyphthalate, 2,5-dimethyl-2,5-di(benzoylperoxy)hexane, 2,5-dimethyl-2,5-di(benzoylperoxy)-3-hexyne, methyl ethyl ketone peroxide, cyclohexanone peroxide, azobisisobutyronitrile and azobis(2,4-dimethylvaleronitrile).

10. The crosslinking agent composition for olefin copolymers according to claim 1, wherein The silane coupling agent is one or more selected from N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane, N-(β-aminoethyl)-γ-aminopropylmethyldimethoxysilane, γ-aminopropyltriethoxysilane, γ-glycidoxypropyltrimethoxysilane, γ-methacryloxypropyltrimethoxysilane, vinyltrimethoxysilane, vinyltriethoxysilane, 3-methacryloxypropylmethyldimethoxysilane, 3-methacryloxypropylmethyldiethoxysilane, 3-methacryloxypropyltriethoxysilane and p-phenylenetrimethoxysilane.

11. A sealant composition for an optical device, the composition comprising: Olefin copolymers; and The crosslinking agent composition for olefin copolymers according to claim 1.

12. The sealant composition for an optical device according to claim 11, wherein The olefin copolymer is an ethylene α-olefin copolymer.

13. A sealing film for an optical device, the sealing film comprising a structure derived from an olefin-based copolymer and a compound of the following Formula 1: [Formula 1] In formula 1, R1 to R4 are each independently an alkyl group of 1 to 20 carbon atoms or an alkenyl group of 2 to 20 carbon atoms, m is an integer of 1 to 20.

14. A photovoltaic device comprising an optical device and the sealing film for an optical device according to claim 13.

Citation Information

Patent Citations

  • Water-proof pack for a firearm

    KR1020220085134A